Implementing an Electronic Medical Record Osteoporosis Self-Assessment Tool Score Which Identifies Patients at Risk for Osteoporosis Promotes Osteoporosis Evaluation. (24th March 2021) - Johnson, Taylor; Fox, Edward; Hassanbein, Sue
Introduction: Osteoporosis affects nearly half of the U.S. population. Screening methods are improving but remain inadequate, leaving the disease underdiagnosed and undertreated. The purpose of this study is to determine the effectiveness of an EMR implemented system that identifies patients at risk for osteoporosis via an OST (osteoporosis screening tool) score in prompting patients toward osteoporosis evaluation. Methods: OST scores are generated on every patient 50 years of age and older that is admitted to the Penn State Hershey Medical Center (PSHMC) and recorded in their electronic medical record. An OST score < 2 indicates that a patient has a potential risk for osteoporosis. Information Technology (IT) implemented the EMR OST calculation, which currently generates a daily filtered list of all patients with an OST score <2; patients with an OST score < 2 are then mailed letters approximately 3 months after their admission informing them of their risk for osteoporosis and suggesting that they schedule a follow-up appointment with a physician for further evaluation. To test the effectiveness of this system in prompting patients toward osteoporosis evaluation, approximately 3 months after letters were mailed, the patients were contacted via telephone and asked a series of questions to determine if the patients had sought osteoporosis evaluation. Results: In the intervention group, 67 (58.26%) of 115 did not schedule a follow-up, while the remaining 48 (41.74%) did seek a follow-up. Thus, the patient follow-up response rate improved with letter intervention using the OST score as an indicator (P < .0001) compared to historical controls (14.29%). Conclusion: Implementing an EMR OST score which identifies patients at risk for osteoporosis, which generates an automatic letter to the patient, significantly promotes patient driven osteoporosis evaluation compared to historical controls.